Semi-analytic forecasts for Roman – the beginning of a new era of deep-wide galaxy surveys. Issue 1 (8th December 2022) - Yung, L Y Aaron; Somerville, Rachel S; Finkelstein, Steven L; Behroozi, Peter; Davé, Romeel; Ferguson, Henry C; Gardner, Jonathan P; Popping, Gergö; Malhotra, Sangeeta; Papovich, Casey; Rhoads, James E; Bagley, Micaela B; et al.
ABSTRACT: The Nancy Grace Roman Space Telescope, NASA's next flagship observatory, will redefine deep-field galaxy survey with a field of view two orders of magnitude larger than Hubble and an angular resolution of matching quality. These future deep-wide galaxy surveys necessitate new simulations to forecast their scientific output and to optimize survey strategies. In this work, we present five realizations of 2-deg 2 light cones, containing a total of ≳25 million simulated galaxies with −16 ≳ M UV ≳ −25 spanning z ∼ 0 to 10. This data set enables a new set of experiments with the impacts of survey size on the derived galaxy formation and cosmological constraints. The intrinsic and observable galaxy properties are predicted using a well-established, physics-based semi-analytic modelling approach. We provide forecasts for number density, cosmic SFR, field-to-field variance, and angular two-point correlation functions, and demonstrate how the future wide-field surveys will be able to improve these measurements relative to current generation surveys. We also present a comparison between these light cones and others that have been constructed with empirical models. The mock light cones are designed to facilitate the exploration of multi-instrument synergies and connecting with current generation instruments and legacy surveys. In addition to Roman, we also provide photometry for a number of other instruments on upcoming facilities, including Euclid and Rubin, as well as the instruments, that are part of many legacy surveys. Full object catalogues and data tables for the results presented in this work are made available through a web-based, interactive portal.